Advanced RFID systems, security, and applications - Karmakar, Nemai Chandra, 1963- (Information Science Reference, 2013)
"This book features a comprehensive collection of research provided by leading experts in both academia and industries, providing state-of-the-art development on RFID"--Provided by publisher.
Keywords: Radio frequency identification systems.; elektronické knihy; electronic books